Assessing the Intrinsic Activity of Pt‐Group Electrocatalysts for Carbon Monoxide Oxidation: Best Practices and Benchmarking Parameters - Kamel Eid (1542562) (2024)
Pt-group elements are the state-of-the-art electrocatalysts for various fuel cells. However, their CO-poising is a critical hitch for large-scale applications, so the researchers are exerting huge efforts to solve this issue. The exponentially increasing attention in this field pressures the researchers to publish their findings quickly, leading to unavoidable flawed evaluation parameters for the intrinsic activity of electrocatalysts. The CO oxidation (COOxid) is highly sensitive to various factors. Thus, it is urgent to afford a deeper understanding of the inherent COOxid activity of state-of-the-art electrocatalysts and adopt accurate guidelines for researchers to test, optimize, and compare their electrocatalysts. This review provides exactitude in the evaluation and precise assessment of the key descriptors related to electrocatalysts (i. e., effect of both size, shape, and support) and CO oxidation (i. e., effect of electrolyte, working electrode, and CO surface diffusion). This is besides the fundamental aspects (i. e., COOxid Process, mechanism, measurements, calculations, thermodynamics, and kinetics). Various experimental results from our group and others besides in-situ analysis were provided to support our deep discussion. Finally, we provide a brief synopsis of the relevant milestones of the up-to-date challenges and perspectives. Other Information Published in: ChemCatChem License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/cctc.202301747